Limited Efficiency of Monetary Policy on Local Inflation Rates and Output - Mendoza Vargas, Oscar Manuel (2023)
This is the second article of a series of two that documents the limited efficiency of the Peruvian monetary policy on local inflation rates. With this research I deepen on my preliminary findings on the unobserved effects of Peruvian monetary policy using departmental Phillips curves. On this occasion, the motivation seeks to answer the question: by incorporating the NAIRU-Keynesian and neo-Keynesian structural model criteria for the Peruvian case, what other unobserved effects of monetary policy would be found in Peru’s departments? Two models of structural equations are developed to estimate the impact of monetary policy at sub-national levels, the first considers the unemployment rate (NAIRU-Keynesian) and the second considers the departmental GDP gap, from which there are counterproductive results that start from the misalignment of departmental economic cycles with the national one which generates inefficiency of monetary policy to reduce departmental inflation, the increase in departmental unemployment and the decrease in the departmental GDP gap.